Pelaksanaan Diversi Terhadap Anak Yang Berhadapan Dengan Hukum(Studi Kasus Terhadap Penetapan Di Wilayah Pengadilan Negeri Surakarta) - Santoso, Budi, Kuswardani, S.H., M.Hum (2017)
The aims of this research are to find out about arrangement of a child dealing with law in the positive criminal law, diversion mechanism with restorative justice approaches and consideration of the law by law enforcement officers from the normative side. This research including the types of legal research methods with normative case approach and secondary type data with research that uses the setting of District court of Surakarta Number: 01-Pen. PID. Diversion/2016/ URURPN.skt and number: 08/Pen. PID. Versioned/2016/URURPN.skt. Based on research results that the children diversion arrangements dealing with law in the Constitution, be found in UUD 1945, UU Children protection UU number 11 year 2012 children's criminal justice system and Government Regulation number 65 year 2015. In the mechanism of diversion in its implementation using a model of victim-offender mediation and informal and in consideration of the law enforcement agencies there is consideration of juridical, sociological and philosophical.